A flame retardant, antistatic and highly wear-resistant epoxy powder coating and its preparation process

The existing solutions are solved by using a combination of bisphenol A epoxy resin, a phenolic modified resin and a brominated resin in powder coatings, as well as composite fillers and modified carbon blacks of molybdenum disulfide, electrolytetrafluoroethylene and polytetrafluoroethylene. The lack of powder coatings in flame retardancy, antistatic properties, waterproof properties and aging resistance has achieved higher performance coating applications.

CN118755362BActive Publication Date: 2024-12-24SHANDONG HENGXIN COMPOSITE MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411153907.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2024-12-24
Estimated Expiration
2044-08-21

AI Technical Summary

Technical Problem

Existing powder coatings cannot balance the higher demands of flame retardancy, antistatic, waterproof and aging resistance in the fields of equipment corrosion protection, pipeline coating and automotive parts.

Method used

Using a combination of bisphenol A epoxy resin, phenolic modified resin and brominated resin, combined with composite fillers of molybdenum disulfide, electrolytetrafluoroethylene, and modified carbon black as functional additives, through specific resins Combination and filler combination enhance the three-dimensional network structure and electronic flow path of the coating layer, and improve the waterproof, corrosion-proof and mechanical properties of the coating.

Benefits of technology

It achieves excellent flame retardant, anti-static, waterproof and aging resistance of coatings, meets higher performance diversity needs, and significantly improves application performance in the fields of equipment corrosion protection, pipeline coating and automotive parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the field of epoxy powder coatings, and in particular to a flame retardant, antistatic, and highly wear-resistant epoxy powder coating and its preparation process. The flame retardant, antistatic, and highly wear-resistant epoxy powder coating, in parts by mass, has the following raw materials: 20 to 40 parts of bisphenol A epoxy resin, 20 to 30 parts of phenolic modified resin, 20 to 25 parts of brominated resin, 20 to 25 parts of curing agent, 45 to 60 parts of functional filler, 8 to 15 parts of functional additives, and 3 to 5 parts of dispersant. The epoxy powder coating prepared in the present application can not only have excellent flame retardant and antistatic properties, but also maintain excellent waterproof, aging resistance, and mechanical properties, meeting the needs of existing equipment anti-corrosion, pipeline coatings, and automotive parts for higher performance diversity of powder coatings, and has very excellent application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of epoxy powder coatings, and in particular to a flame retardant, antistatic and highly wear-resistant epoxy powder coating and a preparation process thereof. Background Art

[0002] Powder coating is a kind of coating in the form of solid powder, which is different from traditional liquid coating. It is usually composed of resin, curing agent, pigment and filler, and does not need solvent dilution before use. Powder coating is applied to the pre-treated metal or other substrate surface by electrostatic spraying or fluidized bed dipping, and then heated in an oven to melt and solidify to form a smooth coating.

[0003] With the increasing awareness of environmental protection and the requirements for industrial production efficiency, powder coatings have been widely used due to their low volatile organic compound (VOC) emissions, high coating efficiency and excellent coating performance, especially in equipment anti-corrosion, pipeline coatings, automotive parts, building materials and other industries. With the continuous development and research and development of the corresponding industrial fields, the demand and requirements for epoxy powder coatings are also increasing. Especially in the fields of equipment anti-corrosion, pipeline coatings and automotive parts, there are more and higher requirements for the flame retardancy, antistatic, waterproof and aging resistance of powder coatings, and the existing powder coating products cannot meet the above diverse needs in a balanced manner.

[0004] Therefore, in order to solve the above problems, the present application provides a flame retardant, antistatic and highly wear-resistant epoxy powder coating and a preparation process thereof. The epoxy powder coating prepared in the present application not only has excellent flame retardant and antistatic properties, but also can maintain excellent waterproof, aging resistance and mechanical properties, meeting the needs of existing fields such as equipment corrosion protection, pipeline coatings and automotive parts for higher performance diversity of powder coatings, and has very excellent application prospects. Summary of the invention

[0005] In order to solve the above problems, the first aspect of the present application provides a flame retardant, antistatic and highly wear-resistant epoxy powder coating. The raw materials are, by mass: 20 to 40 parts of bisphenol A epoxy resin, 20 to 30 parts of phenolic modified resin, 20 to 25 parts of brominated resin, 20 to 25 parts of curing agent, 45 to 60 parts of functional filler, 8 to 15 parts of functional additives, and 3 to 5 parts of dispersant.

[0006] As a preferred embodiment, the mass ratio of the bisphenol A epoxy resin, the phenolic modified resin and the brominated resin is (25-35): (22-26): (21-24).

[0007] As a preferred embodiment, the mass ratio of the bisphenol A epoxy resin, the phenolic modified resin and the brominated resin is (28-30): (23-25): (21-23).

[0008] As a preferred solution, the mass ratio of the bisphenol A epoxy resin, the curing agent and the functional additive is (25-35): (20-23): (10-14).

[0009] As a preferred embodiment, the mass ratio of the bisphenol A epoxy resin, the curing agent and the functional additive is (28-30): (21-22): (11-12).

[0010] As a preferred solution, the epoxy equivalent of the bisphenol A epoxy resin is 800-950 g / eq.

[0011] As a preferred solution, the epoxy equivalent of the bisphenol A epoxy resin is 840-900 g / eq.

[0012] As a preferred solution, the acid value of the bisphenol A epoxy resin is 10-25 mgKOH / g.

[0013] As a preferred solution, the acid value of the bisphenol A epoxy resin is 14-22 mgKOH / g.

[0014] As a preferred solution, the phenolic modified resin is a phenolic modified epoxy resin.

[0015] As a preferred solution, the epoxy equivalent of the phenolic modified epoxy resin is 700-900 g / eq.

[0016] As a preferred solution, the epoxy equivalent of the phenolic modified epoxy resin is 740-830 g / eq.

[0017] As a preferred solution, the viscosity of the phenolic modified epoxy resin is 20000-50000 mPa·s at 25°C.

[0018] As a preferred solution, the viscosity of the phenolic modified epoxy resin is 30000-40000 mPa·s at 25°C.

[0019] As a preferred solution, the functionality of the phenolic modified epoxy resin is 2.6 to 2.8.

[0020] As a preferred solution, the softening point of the phenolic modified epoxy resin is 100-120°C.

[0021] As a preferred solution, the brominated resin is brominated bisphenol A epoxy resin.

[0022] As a preferred solution, the epoxy equivalent of the brominated resin is 700-850 g / eq.

[0023] As a preferred solution, the epoxy equivalent of the brominated resin is 720-820 g / eq.

[0024] As a preferred solution, the softening point of the brominated resin is 100-110°C.

[0025] As a preferred solution, the bromine content of the brominated resin is 48-52%.

[0026] In this application, by adopting the above-mentioned specific resin combination scheme, the antistatic, waterproof, aging and corrosion resistance of epoxy powder coating can be effectively improved. The combination of the above-mentioned bisphenol A epoxy resin, phenolic modified epoxy resin and brominated epoxy resin can not only greatly enhance the construction speed and strength of the three-dimensional network structure in the coating layer through the entanglement of the segments with different active site amounts, but also increase the density of the segments inside the coating system, thereby greatly increasing the free resistance of water molecules and free groups inside the coating, thereby reducing the contact, collision and combination probability between them, thereby obtaining good system stability, improving waterproof, corrosion and mechanical effects; on the other hand, it can also greatly enhance the integration effect of solid particles in the overall powder coating through its adhesion to different particles added in this application, so that the solid particles can build a good continuous connection system by relying on different particle size combinations, thereby forming a good functional particle path in the system, enhancing the electron transmission speed and dissipation effect, and enhancing the flame retardant assistance effect of the system, thereby enhancing the various properties of the system through the combination of resins.

[0027] As a preferred solution, the curing agent is at least one of dicyandiamide, 2-ethyl-4-methylimidazole, 2-methylimidazole, and 2-phenylimidazole.

[0028] As a preferred solution, the curing agent is 2-methylimidazole.

[0029] As a preferred solution, the functional filler is a composition of molybdenum disulfide, electrolytic quartz powder and polytetrafluoroethylene.

[0030] As a preferred solution, the mass ratio of molybdenum disulfide, electrolytic quartz powder and polytetrafluoroethylene is (10-15): (30-35): (5-10).

[0031] As a preferred solution, the mass ratio of molybdenum disulfide, electrolytic quartz powder and polytetrafluoroethylene is (12-14): (32-34): (6-8).

[0032] As a preferred solution, the average particle size of the molybdenum disulfide is 1-1.5 μm.

[0033] As a preferred solution, the average particle size of the electrolytic quartz powder is 0.5-1 μm.

[0034] As a preferred solution, the average particle size of the polytetrafluoroethylene is 0.3-0.6 μm.

[0035] In this application, the addition of the above-mentioned composite filler can effectively improve the mechanical, flame retardant, anti-corrosion and waterproof effects of the epoxy powder coating. The layered structure of molybdenum disulfide can form a lubricating film in the coating system, thereby effectively reducing the roughness of the coating surface and forming a relatively flat and smooth surface. The film structure and molybdenum disulfide greatly enhance the barrier effect on corrosive molecules, and obtain good flame retardant and anti-corrosion effects; and by adding an appropriate amount of electrolytic quartz powder and polytetrafluoroethylene, the mechanical properties of the coating system can be enhanced through pores and group connection effects, and by controlling their respective contents and particle sizes, the molecular chain breakage of the particles in the epoxy resin system caused by their addition is avoided, thereby ensuring the performance of the powder coating system.

[0036] As a preferred solution, the functional additive is modified carbon black.

[0037] As a preferred solution, the preparation method of the modified carbon black comprises the following steps: S1: adding zinc oxide, succinic anhydride and zinc nitrate hexahydrate to a DMF solution, heating the mixture to 50-55°C and keeping the mixture for 30-45 minutes, then adding a DMF solution of 2,5-dihydroxyterephthalic acid, heating the mixture to 65-70°C and keeping the mixture for 3-4 hours; S2: adding the carbon black mixture to a DMF solvent, then adding citric acid and triisostearyl titanate isopropyl, mixing the mixture and dispersing the mixture by ultrasonication at a power of 200-300W for 1-1.5 hours, then dispersing the obtained mixture by ultrasonication. The acoustic dispersion liquid is added to the reaction solution obtained in S1, and the reaction is continued at 65-70°C for 2-3 hours; S3: After the reaction of S2 is completed, ammonia water is added to adjust the pH of the reaction solution to 9-9.5, and then an ethanol solution of tetraethyl orthosilicate is added, and the temperature is lowered to 55-60°C and the reaction is maintained for 1.5-2 hours; S4: In a closed reactor, the temperature is raised to 120-130°C under a nitrogen atmosphere, and the reaction is stirred at 160-200 rpm for 22-26 hours. After the reaction is completed, the product is centrifuged and filtered, and washed with methanol and deionized water for 2-3 times in a cycle, and then dried.

[0038] As a preferred solution, the mass ratio of zinc oxide, succinic anhydride, zinc nitrate hexahydrate and 2,5-dihydroxyterephthalic acid is (0.8-1.2): (2.1-2.6): (1.2-1.5): (3-3.2).

[0039] As a preferred solution, the mass ratio of the carbon black, citric acid, isopropyl triisostearyl titanate and tetraethyl orthosilicate is (4.5-5.5): (1.4-1.5): (0.5-0.7): (1.2-1.4).

[0040] As a preferred solution, the mass ratio of zinc oxide to carbon black is (1-1.1): (4.8-5.2).

[0041] As a preferred solution, the average particle size of the carbon black is 20-30 nm.

[0042] As a preferred solution, the average particle size of the zinc oxide is 10-15 nm.

[0043] As a preferred solution, the average particle size of the modified carbon black is 580-680 nm.

[0044] The modified carbon black added in the present application can greatly improve the antistatic, flame retardant, waterproof and aging resistance of the powder coating system. The added modified carbon black can greatly increase the length of its own electron flow path through the composite structure formed by it, and through the surface modification effect, it can strengthen the attraction and connection effect with the epoxy resin, thereby forming a continuous ladder distribution in the system, thereby further extending the electron path, and greatly enhancing the antistatic dissipation effect of the powder coating. The good terraced distribution effect formed can greatly help enhance the barrier effect of the coating system on water molecules and free radicals, greatly increase the length of the moving route required for their penetration, and thus maintain excellent waterproof and anti-corrosion permeability during long-term use. On the coating surface, the surface flat structure of the framework particles formed in the modified carbon black can interact with other functional fillers to promote the formation of a coating surface with lower surface energy, avoiding the acceleration effect of the overly rugged surface structure on the formation of the surface hydration layer, and even if some water molecules penetrate in, the strong adsorption structure of the framework particles can adsorb water molecules and large active molecules in the first time, play a good internal cleaning role, and can always play a stable molecular preservation role under a limited temperature environment, thereby obtaining excellent performance.

[0045] As a preferred solution, the dispersant is at least one of D-346, BYK-190, BYK-163, lauryl alcohol polyoxyethylene ether, cetearyl alcohol polyoxyethylene ether, and coconut oil betaine.

[0046] As a preferred solution, the dispersant is at least one of BYK-190, BYK-163 or lauryl alcohol polyoxyethylene ether.

[0047] The second aspect of the present application provides a method for preparing the above-mentioned flame-retardant, antistatic and highly wear-resistant epoxy powder coating, and the specific steps include: S1: weigh bisphenol A epoxy resin, phenolic modified resin and brominated resin, and pre-stir and mix them evenly until there is no stratification and no discoloration to obtain a mixed resin; S2: then add the mixed resin to a high-speed mixer, and add the remaining raw materials in sequence, and mix them evenly at a high speed of 400~500rpm to obtain a premix; S3: add the premix to a granulator, heat, extrude and water-cool granulate, the heating and extrusion temperature is 120~140℃, the water cooling tank temperature is 50~55℃, the obtained particles are naturally cooled to room temperature, and ground and sieved to obtain.

[0048] The beneficial effects of this application are:

[0049] 1. The flame retardant, antistatic and highly wear-resistant epoxy powder coating provided in the present application not only has excellent flame retardant and antistatic properties, but also can maintain excellent waterproof, aging resistance and mechanical properties, meeting the needs of existing fields such as equipment anti-corrosion, pipeline coatings and automotive parts for higher performance diversity of powder coatings, and has very excellent application prospects.

[0050] 2. A flame retardant, antistatic and highly wear-resistant epoxy powder coating provided in the present application can effectively improve the antistatic, waterproof, aging-resistant and corrosion-resistant properties of the epoxy powder coating by adopting a specific resin combination scheme; the combination of bisphenol A epoxy resin, phenolic modified epoxy resin and brominated epoxy resin can not only greatly enhance the construction speed and strength of the three-dimensional network structure in the coating layer through the entanglement of chain segments with different active site amounts, but also increase the density of the chain segments inside the coating system, thereby greatly increasing the free resistance of water molecules and free groups inside the coating, thereby reducing the contact, collision and combination probability between them, thereby obtaining good system stability and improving the waterproof, anti-corrosion and mechanical effects.

[0051] 3. A flame-retardant, antistatic and highly wear-resistant epoxy powder coating provided in the present application, the addition of its composite filler can effectively improve the mechanical, flame-retardant, anti-corrosion and waterproof effects of the epoxy powder coating, and the layered structure of molybdenum disulfide can form a lubricating film in the coating system, thereby effectively reducing the roughness of the coating surface, forming a relatively smooth surface, and greatly enhancing the barrier effect on corrosive molecules through the film structure and molybdenum disulfide, thereby obtaining good flame-retardant and anti-corrosion effects; and through the addition of appropriate amounts of electrolytic quartz powder and polytetrafluoroethylene, the mechanical properties of the coating system can be enhanced through pores and group connection effects, and by controlling their respective contents and particle sizes, the molecular chain breakage of the particles in the epoxy resin system caused by their addition is avoided, thereby ensuring the performance of the powder coating system.

[0052] 4. The flame-retardant, antistatic, and highly wear-resistant epoxy powder coating provided in the present application, the modified carbon black can greatly improve the antistatic, flame-retardant, waterproof and aging-resistant properties of the powder coating system. The added modified carbon black can greatly enhance the length of its own electron flow path through the composite structure formed by it, and through the surface modification effect, it can strengthen the attraction and connection effect with the epoxy resin, thereby forming a continuous ladder distribution in the system, thereby further extending the electron path, and greatly enhancing the antistatic dissipation effect of the powder coating. And the good ladder distribution effect formed can greatly help enhance the barrier effect of the coating system for water molecules and free radicals, greatly increase the length of the mobile route required for its penetration, and thus maintain excellent waterproof and anti-corrosion permeability during long-term use. DETAILED DESCRIPTION

[0053] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.

[0054] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.

[0055] Example 1: Example 1 The first aspect provides a flame retardant, antistatic and highly wear-resistant epoxy powder coating. The raw materials are, by mass: 29.5 parts of bisphenol A epoxy resin, 24.5 parts of phenolic modified resin, 22.3 parts of brominated resin, 21.4 parts of curing agent, 52 parts of functional filler, 11.8 parts of functional additives, and 4.5 parts of dispersant.

[0056] The functional filler is a composition of molybdenum disulfide, electrolytic quartz powder and polytetrafluoroethylene, and the mass ratio of molybdenum disulfide, electrolytic quartz powder and polytetrafluoroethylene is 13:32:7.

[0057] The average particle size of molybdenum disulfide is 1.1 μm, purchased from Luoyang Shenyu Molybdenum Co., Ltd., China; the average particle size of electrolytic quartz powder is 0.8 μm, purchased from Xuzhou Inno New Materials Co., Ltd., China; the average particle size of polytetrafluoroethylene is 0.42 μm, purchased from Hubei Langbowan Co., Ltd., China.

[0058] The bisphenol A epoxy resin has an epoxy equivalent of 864 g / eq and an acid value of 20 mgKOH / g and is purchased from Zhuhai Hongchang Electronic Materials Co., Ltd., China, as a 904H product.

[0059] The phenolic modified resin is a phenolic modified epoxy resin, with an epoxy equivalent of 788 g / eq, a viscosity of 32000 mPa·s, a functionality of 2.6 at 25° C., and a softening point of 110° C. It is purchased from Dow Chemical of the United States and is a DER672U product.

[0060] The brominated resin is brominated bisphenol A epoxy resin, with an epoxy equivalent of 745 g / eq, a softening point of 105° C., and a bromine content of 51%. It was purchased from the NPEB-408 model product sold by Nan Ya Company in Taiwan, China.

[0061] The curing agent is 2-methylimidazole.

[0062] The functional additive is modified carbon black. The preparation method of modified carbon black comprises the following steps, calculated by mass: S1: 1.05 parts of zinc oxide, 2.4 parts of succinic anhydride and 1.4 parts of zinc nitrate hexahydrate are mixed and added to 80 parts of DMF solution, heated to 55°C and kept warm for 35 minutes, then 3.08 parts of DMF solution of 2,5-dihydroxyterephthalic acid (30 parts in total) are added, heated to 70°C and kept warm for 4 hours; S2: 4.98 parts of carbon black are mixed and added to 60 parts of DMF solvent, then 1.44 parts of citric acid and 0.61 parts of triisostearyl titanate are mixed and stirred for 2 hours. After the combination, ultrasonic dispersion was carried out at 250W power for 1h, and then the obtained ultrasonic dispersion was added to the reaction solution obtained in S1, and the reaction was continued at 68°C for 2.5h; S3: After the reaction of S2 was completed, ammonia water was added to adjust the pH of the reaction solution to 9.1, and then 1.22 parts of ethanol solution of tetraethyl orthosilicate (a total of 15 parts) were added, and the temperature was lowered to 58°C and the reaction was kept warm for 2h; S4: In a closed reactor, the temperature was raised to 128°C under a nitrogen atmosphere, and the reaction was stirred at 180rpm for 23.5h. After the reaction was completed, the product was centrifuged and filtered, and washed with methanol and deionized water for 3 times in a cycle, and then dried.

[0063] The average particle size of carbon black is 28.5 nm, and the product with the corresponding particle size is purchased from Mitsubishi Corporation of Japan; the average particle size of zinc oxide is 12.2 nm.

[0064] The average particle size of the modified carbon black is 644 nm.

[0065] The dispersant is BYK-190.

[0066] The second aspect of the present embodiment provides a method for preparing the above-mentioned flame-retardant, antistatic and highly wear-resistant epoxy powder coating, and the specific steps include: S1: weigh bisphenol A epoxy resin, phenolic modified resin and brominated resin, and pre-stir and mix them evenly until there is no stratification and no discoloration to obtain a mixed resin; S2: then add the mixed resin to a high-speed mixer, and add the remaining raw materials in sequence, and mix them evenly at a high speed of 450 rpm to obtain a premix; S3: add the premix to a granulator, heat, extrude and water-cool granulate, the heating extrusion temperature is 125°C, the water cooling tank temperature is 52°C, the obtained particles are naturally cooled to room temperature, and are ground and sieved to obtain.

[0067] Example 2: Example 2 The first aspect provides a flame retardant, antistatic and highly wear-resistant epoxy powder coating. The raw materials, in parts by mass, are: 34.5 parts of bisphenol A epoxy resin, 22 parts of phenolic modified resin, 24 parts of brominated resin, 20.5 parts of curing agent, 54 parts of functional filler, 13.8 parts of functional additives, and 3.6 parts of dispersant.

[0068] The functional filler is a composition of molybdenum disulfide, electrolytic quartz powder and polytetrafluoroethylene, and the mass ratio of molybdenum disulfide, electrolytic quartz powder and polytetrafluoroethylene is 14:34:6.

[0069] The average particle size of molybdenum disulfide is 1.1 μm, purchased from Luoyang Shenyu Molybdenum Co., Ltd., China; the average particle size of electrolytic quartz powder is 0.8 μm, purchased from Xuzhou Inno New Materials Co., Ltd., China; the average particle size of polytetrafluoroethylene is 0.42 μm, purchased from Hubei Langbowan Co., Ltd., China.

[0070] The bisphenol A epoxy resin has an epoxy equivalent of 864 g / eq and an acid value of 20 mgKOH / g and is purchased from Zhuhai Hongchang Electronic Materials Co., Ltd., China, as a 904H product.

[0071] The phenolic modified resin is a phenolic modified epoxy resin, with an epoxy equivalent of 788 g / eq, a viscosity of 32000 mPa·s, a functionality of 2.6 at 25° C., and a softening point of 110° C. It is purchased from Dow Chemical of the United States and is a DER672U product.

[0072] The brominated resin is brominated bisphenol A epoxy resin, with an epoxy equivalent of 745 g / eq, a softening point of 105° C., and a bromine content of 51%. It was purchased from the NPEB-408 model product sold by Nan Ya Company in Taiwan, China.

[0073] The curing agent is 2-methylimidazole.

[0074] The functional additive is modified carbon black. The preparation method of modified carbon black comprises the following steps, calculated by mass: S1: 1.05 parts of zinc oxide, 2.4 parts of succinic anhydride and 1.4 parts of zinc nitrate hexahydrate are mixed and added to 80 parts of DMF solution, heated to 55°C and kept warm for 35 minutes, then 3.08 parts of DMF solution of 2,5-dihydroxyterephthalic acid (30 parts in total) are added, heated to 70°C and kept warm for 4 hours; S2: 4.98 parts of carbon black are mixed and added to 60 parts of DMF solvent, then 1.44 parts of citric acid and 0.61 parts of triisostearyl titanate are mixed and stirred for 2 hours. After the combination, ultrasonic dispersion was carried out at 250W power for 1h, and then the obtained ultrasonic dispersion was added to the reaction solution obtained in S1, and the reaction was continued at 68°C for 2.5h; S3: After the reaction of S2 was completed, ammonia water was added to adjust the pH of the reaction solution to 9.1, and then 1.22 parts of ethanol solution of tetraethyl orthosilicate (a total of 15 parts) were added, and the temperature was lowered to 58°C and the reaction was kept warm for 2h; S4: In a closed reactor, the temperature was raised to 128°C under a nitrogen atmosphere, and the reaction was stirred at 180rpm for 23.5h. After the reaction was completed, the product was centrifuged and filtered, and washed with methanol and deionized water for 3 times in a cycle, and then dried.

[0075] The average particle size of carbon black is 28.5 nm, and the product with the corresponding particle size is purchased from Mitsubishi Corporation of Japan; the average particle size of zinc oxide is 12.2 nm.

[0076] The average particle size of the modified carbon black is 644 nm.

[0077] The dispersant is BYK-190.

[0078] The second aspect of the present embodiment provides a method for preparing the above-mentioned flame-retardant, antistatic and highly wear-resistant epoxy powder coating, and the specific steps include: S1: weigh bisphenol A epoxy resin, phenolic modified resin and brominated resin, and pre-stir and mix them evenly until there is no stratification and no discoloration to obtain a mixed resin; S2: then add the mixed resin to a high-speed mixer, and add the remaining raw materials in sequence, and mix them evenly at a high speed of 450 rpm to obtain a premix; S3: add the premix to a granulator, heat, extrude and water-cool granulate, the heating extrusion temperature is 125°C, the water cooling tank temperature is 52°C, the obtained particles are naturally cooled to room temperature, and are ground and sieved to obtain.

[0079] Comparative Example 1

[0080] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the flame retardant, antistatic and highly wear-resistant epoxy powder coating, in parts by mass, the raw materials are: 45.8 parts of bisphenol A epoxy resin, 11.2 parts of phenolic modified resin, 10.3 parts of brominated resin, 24.2 parts of curing agent, 52 parts of functional filler, 11.8 parts of functional additives, and 4.5 parts of dispersant.

[0081] Comparative Example 2

[0082] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the flame retardant, antistatic and highly wear-resistant epoxy powder coating, in parts by mass, the raw materials are: 21.2 parts of bisphenol A epoxy resin, 35.5 parts of phenolic modified resin, 32.8 parts of brominated resin, 23.4 parts of curing agent, 52 parts of functional filler, 11.8 parts of functional additives, and 4.5 parts of dispersant.

[0083] Comparative Example 3

[0084] The specific implementation of this comparative example is basically the same as that of Example 1, except that the epoxy equivalent of bisphenol A epoxy resin is 1080 g / eq, the acid value is 32 mgKOH / g, and it is purchased from Zhuhai Hongchang Electronic Materials Co., Ltd., China.

[0085] Comparative Example 4

[0086] The specific implementation method of this comparative example is basically the same as that of Example 1, except that the phenolic modified resin is a phenolic modified epoxy resin with an epoxy equivalent of 642 g / eq, a viscosity of 18000 mPa·s, a functionality of 2.2, and a softening point of 102°C, which was purchased from Suzhou Senfida Chemical Co., Ltd., China.

[0087] Comparative Example 5

[0088] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified carbon black comprises the following steps, calculated by mass: S1: 0.35 parts of zinc oxide, 3.5 parts of succinic anhydride and 2.2 parts of zinc nitrate hexahydrate are mixed and added to 120 parts of DMF solution, heated to 55°C and kept warm for 35 minutes, then 4.5 parts of DMF solution of 2,5-dihydroxyterephthalic acid (30 parts in total) are added, heated to 70°C and kept warm for 4 hours; S2: 4.98 parts of carbon black are mixed and added to 60 parts of DMF solvent, then 1.44 parts of citric acid and 0.61 parts of triisostearate are added, After the fatty acyl titanate isopropyl is mixed, it is ultrasonically dispersed at 250W for 1h, and then the obtained ultrasonic dispersion is added to the reaction solution obtained in S1, and the reaction is continued at 68°C for 2.5h; S3: After the reaction of S2 is completed, ammonia water is added to adjust the pH of the reaction solution to 9.1, and then 1.22 parts of ethanol solution of tetraethyl orthosilicate (15 parts in total) are added, and the temperature is lowered to 58°C and the reaction is kept for 2h; S4: In a closed reactor, the temperature is raised to 128°C under a nitrogen atmosphere, and the reaction is stirred at 180rpm for 23.5h. After the reaction is completed, the product is centrifuged and filtered, and washed with methanol and deionized water for 3 times in a cycle, and then dried.

[0089] The average particle size of the modified carbon black is 812 nm.

[0090] Comparative Example 6

[0091] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified carbon black comprises the following steps, calculated by mass: S1: 1.05 parts of zinc oxide, 1.2 parts of succinic anhydride and 1.4 parts of zinc nitrate hexahydrate are mixed and added to 80 parts of DMF solution, heated to 55°C and kept warm for 35 minutes, then 3.08 parts of DMF solution of 2,5-dihydroxyterephthalic acid (30 parts in total) are added, heated to 70°C and kept warm for 4 hours; S2: 6.8 parts of carbon black are mixed and added to 100 parts of DMF solvent, then 0.68 parts of citric acid and 0.32 parts of triisostearate are added; After the fatty acyl titanate isopropyl ester is mixed, ultrasonic dispersion is carried out at 250W power for 1h, and then the obtained ultrasonic dispersion is added to the reaction solution obtained in S1, and the reaction is continued at 68°C for 2.5h; S3: After the reaction of S2 is completed, ammonia water is added to adjust the pH of the reaction solution to 9.1, and then 0.71 parts of ethanol solution of tetraethyl orthosilicate (10 parts in total) is added, and the temperature is reduced to 58°C and the reaction is maintained for 2h; S4: In a closed reactor, the temperature is raised to 128°C under a nitrogen atmosphere, and the reaction is stirred at 180rpm for 23.5h. After the reaction is completed, the product is centrifuged and filtered, and washed with methanol and deionized water for 3 times in a cycle, and then dried.

[0092] The average particle size of the modified carbon black is 504 nm.

[0093] Comparative Example 7

[0094] The specific implementation of this comparative example is basically the same as that of Example 1, except that the average particle size of carbon black is 45.5 nm, which is a product of corresponding particle size purchased from Mitsubishi Corporation of Japan; and the average particle size of zinc oxide is 28.4 nm.

[0095] The average particle size of the modified carbon black is 914 nm.

[0096] Comparative Example 8

[0097] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the flame retardant, antistatic and highly wear-resistant epoxy powder coating, in parts by mass, the raw materials are: 38.5 parts of bisphenol A epoxy resin, 24.5 parts of phenolic modified resin, 22.3 parts of brominated resin, 21.4 parts of curing agent, 52 parts of functional filler, 6.5 parts of functional additive, and 4.5 parts of dispersant.

[0098] Comparative Example 9

[0099] The specific implementation of this comparative example is basically the same as that of Example 1, except that the mass ratio of molybdenum disulfide, electrolytic quartz powder and polytetrafluoroethylene is 4.5:44.5:1.

[0100] Comparative Example 10

[0101] The specific implementation of this comparative example is basically the same as that of Example 1, except that the average particle size of the molybdenum disulfide is 2.8 μm, the average particle size of the electrolytic quartz powder is 1.9 μm, and the average particle size of the polytetrafluoroethylene is 1.2 μm.

[0102] Performance Evaluation

[0103] Flame retardancy: The flame retardancy test of the epoxy powder coatings prepared in the examples and comparative examples was carried out with reference to the standard MT113-1995. The test value was based on the specific flaming combustion time. The average value of 10 tests was recorded in Table 1.

[0104] Antistatic property: The antistatic property of the epoxy powder coatings prepared in the examples and comparative examples was tested with reference to standard MT113-1995. The test value was based on the specific resistance. The average value of 10 tests was recorded in Table 1.

[0105] Waterproofness: The epoxy powder coatings prepared in the embodiments and comparative examples were used to prepare sintered coatings with a coating thickness of 1.5 mm. The sintered coatings prepared in the embodiments and comparative examples were tested for surface water contact angles using the sessile drop method with a water concentration of 2 μL for 15 s. The average value of 10 tests was recorded in Table 1.

[0106] Aging resistance: The epoxy powder coatings prepared in the embodiments and comparative examples were used to prepare fused coatings with a coating thickness of 1.5 mm. The coating samples were placed in a constant temperature and humidity chamber at 65±2°C and 75% humidity for 3 months. After 3 months, the samples were taken out for observation. If cracking, oxidation, blistering and shedding occurred, it was considered unqualified, otherwise it was qualified. 50 groups of samples were tested for each embodiment and comparative example, and the qualified rate was recorded in Table 1.

[0107] Abrasion resistance: The epoxy powder coatings prepared in the examples and comparative examples were tested for abrasion resistance according to the standard GB / T 1768-2006, 1kg / 1000r, CS-17 wheel, and the test values ​​were the average of 10 tests and recorded in Table 1.

[0108] Salt spray corrosion resistance: With reference to standard GB / T1771-2007, the epoxy powder coatings prepared in the examples and comparative examples were subjected to salt spray corrosion resistance for 1000 h to observe whether there were blistering, cracking, rust or oxidation. The results are recorded in Table 1.

[0109] Table 1 Performance test results

[0110] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that Examples 1 and 2 of the present application have obvious advantages over comparative examples 1 to 10 in terms of flame retardancy, waterproofness, antistatic performance, wear resistance, aging resistance and salt spray corrosion resistance. This is mainly due to the combined effect of the modified epoxy resin compounding scheme and functional additives and other auxiliary schemes specified in the present application. Comparative examples 1 to 10 did not adopt the technical scheme specified in the present application, resulting in obvious disadvantages in the above-mentioned performance tests, which further proves the necessity of the technical scheme specified in the present application for the technical effect of the present application and solving technical problems.

Claims

1. A flame retardant, antistatic and highly wear-resistant epoxy powder coating, characterized in that: The raw materials are as follows: 20-40 parts of bisphenol A epoxy resin, 20-30 parts of phenolic modified resin, 20-25 parts of brominated resin, 20-25 parts of curing agent, 45-60 parts of functional filler, 8-15 parts of functional additive, and 3-5 parts of dispersant, calculated by weight. The mass ratio of the bisphenol A epoxy resin, the phenolic modified resin and the brominated resin is (25-35): (22-26): (21-24); The epoxy equivalent of the bisphenol A epoxy resin is 800 to 950 g / eq; The acid value of the bisphenol A epoxy resin is 10 to 25 mgKOH / g; The phenolic modified resin is a phenolic modified epoxy resin; The epoxy equivalent of the phenolic modified epoxy resin is 700 to 900 g / eq; the functionality of the phenolic modified epoxy resin is 2.6 to 2.8; the softening point of the phenolic modified epoxy resin is 100 to 120° C.; The brominated resin is brominated bisphenol A epoxy resin; the epoxy equivalent of the brominated resin is 700 to 850 g / eq; the softening point of the brominated resin is 100 to 110° C.; The curing agent is at least one of dicyandiamide, 2-ethyl-4-methylimidazole, 2-methylimidazole, and 2-phenylimidazole; The functional filler is a composition of molybdenum disulfide, electrolytic quartz powder and polytetrafluoroethylene; The mass ratio of molybdenum disulfide, electrolytic quartz powder and polytetrafluoroethylene is (10-15): (30-35): (5-10); The functional additive is modified carbon black; Preparation method of modified carbon black The following steps are involved: S1: Add zinc oxide, succinic anhydride and zinc nitrate hexahydrate to a DMF solution, heat to 50-55°C and keep warm for 30-45 minutes, then add a DMF solution of 2,5-dihydroxyterephthalic acid, heat to 65-70°C and keep warm for 3-4 hours; S2: Add carbon black to a DMF solvent, then add citric acid and isopropyl triisostearyl titanate, mix and ultrasonically disperse at 200-300W for 1-1.5 hours, then add the obtained ultrasonic dispersion to the reaction solution obtained in S1, and continue to keep warm for 2-3 hours at 65-70°C; S3: After the reaction of S2 is completed, add ammonia water to adjust the pH of the reaction solution to 9-9.5, then add an ethanol solution of ethyl orthosilicate, cool to 55-60°C and keep warm for 1.5-2 hours; S4: In a closed reactor, the temperature is raised to 120-130° C. under a nitrogen atmosphere, and the reaction is stirred at 160-200 rpm for 22-26 hours. After the reaction is completed, the product is centrifuged and filtered, and then washed with methanol and deionized water for 2-3 times, and then dried to obtain the product; The mass ratio of zinc oxide, succinic anhydride, zinc nitrate hexahydrate and 2,5-dihydroxyterephthalic acid is (0.8-1.2): (2.1-2.6): (1.2-1.5): (3-3.2); The mass ratio of the carbon black, citric acid, isopropyl triisostearyl titanate and tetraethyl orthosilicate is (4.5-5.5): (1.4-1.5): (0.5-0.7): (1.2-1.4); The mass ratio of the zinc oxide to the carbon black is (1-1.1):(4.8-5.2).

2. The flame retardant, antistatic and highly wear-resistant epoxy powder coating according to claim 1, characterized in that: The mass ratio of the bisphenol A epoxy resin, the curing agent and the functional auxiliary agent is (25-35): (20-23): (10-14).

3. The flame retardant, antistatic and highly wear-resistant epoxy powder coating according to claim 2, characterized in that: The viscosity of the phenolic modified epoxy resin is 20000-50000 mPa·s at 25°C.

4. The flame retardant, antistatic and highly wear-resistant epoxy powder coating according to claim 3, characterized in that: The bromine content of the brominated resin is 48-52%.

5. The flame retardant, antistatic and highly wear-resistant epoxy powder coating according to claim 4, characterized in that: The average particle size of the molybdenum disulfide is 1 to 1.5 μm; the average particle size of the electrolytic quartz powder is 0.5 to 1 μm.

6. The flame retardant, antistatic and highly wear-resistant epoxy powder coating according to claim 5, characterized in that: The average particle size of the polytetrafluoroethylene is 0.3-0.6 μm.

7. The flame retardant, antistatic and highly wear-resistant epoxy powder coating according to claim 6, characterized in that: The average particle size of the carbon black is 20 to 30 nm; the average particle size of the zinc oxide is 10 to 15 nm.

8. The flame retardant, antistatic and highly wear-resistant epoxy powder coating according to claim 7, characterized in that: The average particle size of the modified carbon black is 580-680 nm.

9. The flame retardant, antistatic and highly wear-resistant epoxy powder coating according to claim 8, characterized in that: The dispersant is at least one of D-346, BYK-190, BYK-163, lauryl alcohol polyoxyethylene ether, cetearyl alcohol polyoxyethylene ether, and coconut oil betaine.

10. A process for preparing the flame retardant, antistatic and highly wear-resistant epoxy powder coating according to any one of claims 1 to 9, characterized in that: The specific steps include: S1: weighing bisphenol A epoxy resin, phenolic modified resin and brominated resin, pre-stirring and mixing them evenly until there is no stratification and no different color, so as to obtain a mixed resin; S2: then adding the mixed resin into a high-speed mixer, and adding the remaining raw materials in sequence, mixing them evenly at a high speed of 400-500 rpm to obtain a premix; S3: adding the premix into a granulator, heating, extruding and water-cooling granulation, the heating extrusion temperature is 120-140°C, the water cooling tank temperature is 50-55°C, the obtained particles are naturally cooled to room temperature, and are ground and sieved to obtain the premix.